2023
DOI: 10.1111/1756-185x.14863
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of IgG4‐associated disease caused by COVID‐19: Case report and literature review

Abstract: An increasing number of cases have reported that coronavirus disease 2019 (COVID‐19) can lead to immune system dysregulation and induce autoimmune diseases, but the mechanism is unclear. We treated a patient who presented with an unknown fever after infection with the novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) in 2023. After excluding the possibility of infection, malignancy, and other connective tissue diseases, we considered the diagnosis of IgG4‐related disease in consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…We conducted a literature review of previously reported cases of IgG4-RD following SARS-CoV-2 infection or vaccination (Table 1) (17)(18)(19)(20)(21)(22)(23)(24)(25). We retrieved a total of 9 cases, of which 5 developed symptoms after vaccination and 4 after infection.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a literature review of previously reported cases of IgG4-RD following SARS-CoV-2 infection or vaccination (Table 1) (17)(18)(19)(20)(21)(22)(23)(24)(25). We retrieved a total of 9 cases, of which 5 developed symptoms after vaccination and 4 after infection.…”
Section: Discussionmentioning
confidence: 99%